General and specific toxicity determination of an extract from the plant Rhodiola semenovii Boriss - Korbozova, N.K.; Terletskaya, N.V.; Kudrina, N.O.; Kobylina, T.N.; Kenzhebayeva, Zh.; Shokan, A.K. (Fundamental and Experimental Biology, 2022)
The study of chronic and acute toxicity pharmacological phenomena with occupational symptoms of intoxication provides essential information on therapeutic activity of the drug. An extract of the Rhodiola semenovii Boriss plant was taken to determine toxicity. Phytochemical studies were carried out on the composition of biologically active compounds for medicinal purposes. Based on the statistical data on the chemical composition, substances, such as flavonoids, coumarins, phenolic acids, and polysaccharides, were identified in the root extract of the Rh. semenovii plant. To study the chronic and acute toxicity of the extract, preclinical tests were on outbred laboratory rats. After completion of the experiment of acute and chronic toxicity, animals were slaughtered and peripheral blood samples were obtained for hematological and biochemical blood analysis. In addition, macroscopic studies of laboratory animals were performed. There were morphological-structural changes heart, kidneys, liver, heart, and pancreas. An external examination at the autopsy revealed no changes in the vital organs, as well as the digestive, respiratory, excretory systems. According to the studies carried out, Rh. semenovii does not have general toxic extracts.